1996
DOI: 10.1021/jf9407432
|View full text |Cite
|
Sign up to set email alerts
|

Fate of U-14C-Gelatinized and U-14C-Retrograded Bean Starch in the Rat

Abstract: The fate of retrograded and gelatinized bean starch in the rat was followed using an in vivo radiolabel technique. [U-14 C]Bean starch was obtained by incubating excised unripe pods of broad beans with 14 CO 2 . After extraction and purification, [ 14 C]bean starch was either retrograded or gelatinized and fed to rats by gavage. Rats were housed individually in metabolic cages and were given free access to food and water. After 3 and 18 h of gavage, rats were killed by cervical dislocation and the radioactivit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Animal experiments were performed according to UK Home Office guidelines. Male Wistar Hans rats (∼150 g), previously fed on a stock pelleted diet (CRM(x)), were used for the study 33. Rats (three per group) were dosed by gavage with 0.5 ml of an aqueous suspension of tannins.…”
Section: Methodsmentioning
confidence: 99%
“…Animal experiments were performed according to UK Home Office guidelines. Male Wistar Hans rats (∼150 g), previously fed on a stock pelleted diet (CRM(x)), were used for the study 33. Rats (three per group) were dosed by gavage with 0.5 ml of an aqueous suspension of tannins.…”
Section: Methodsmentioning
confidence: 99%
“…RS can also be estimated by performing a TS assay on rat fecal material; however, this method does not take into account fermentation, which would occur in the rat bowels (Hoover and Zhou ), thus lowering estimated RS. Additionally, RS may also be estimated by labelling the starch fraction with 13 C (Gerrits and others ) or 14 C (Abia and others ) used for feeding trials, thereby allowing the amount of RS to be quantified by the amount of the labeled carbon leaving the test animal relative to the amount that entered.…”
Section: Measurement Of Rsmentioning
confidence: 99%
“…The metabolic transformations of 14 C metabolites produced during degradation of U-14 C-resistant bean starch have been studied in the liver and carcass by comparison with readily digestible U-14 C-gelatinized bean starch. Recent studies on rats fed U-14 C-resistant starch (Abia et al, 1996) have shown that most of the 14 C metabolized by rat tissues was diverted toward carcass (mainly muscle), pelt, and liver. The liver and carcass were therefore chosen for further investigation.…”
Section: Resultsmentioning
confidence: 99%
“…Preparation of U-14 C-Gelatinized and U-14 C-Resistant Bean Starch. Starch was prepared and purified according to the previous description (Abia et al, 1996). [U-14 C]Starch was obtained from half-filled pods of broad beans incubated under 14 CO2.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation